2006
DOI: 10.1523/jneurosci.1851-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Stargazin and Other Transmembrane AMPA Receptor Regulating Proteins Interact with Synaptic Scaffolding Protein MAGI-2 in Brain

Abstract: MAGI-2 [also known as S-SCAM (synaptic scaffolding molecule)] is a multi-PDZ domain scaffolding protein that interacts with several different ligands in brain, including PTEN (phosphatase and tensin homolog), dasm1(dendrite arborization and synapse maturation 1), dendrin, axin, ␤-and ␦-catenin, neuroligin, hyperpolarization-activated cation channels, ␤1-adrenergic receptors, and NMDA receptors. We confirmed that MAGI-2 coimmunoprecipitated with stargazin in vivo from mouse cerebral cortex and used in vitro ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 59 publications
1
68
0
Order By: Relevance
“…The near-complete loss of podocytes and the rapid progression of glomerular disease in Magi-2 Δ/Δ mice are unusual and cannot be explained purely on the basis of nephrin reduction. These findings suggest an additional, nephrin-independent prosurvival role for MAGI-2 in podocytes, perhaps by blocking the proapoptotic signaling properties of dendrin (34), another MAGI-2 interacting protein (35).…”
Section: Discussionmentioning
confidence: 89%
“…The near-complete loss of podocytes and the rapid progression of glomerular disease in Magi-2 Δ/Δ mice are unusual and cannot be explained purely on the basis of nephrin reduction. These findings suggest an additional, nephrin-independent prosurvival role for MAGI-2 in podocytes, perhaps by blocking the proapoptotic signaling properties of dendrin (34), another MAGI-2 interacting protein (35).…”
Section: Discussionmentioning
confidence: 89%
“…Mechanistically, functional cooperation might be mediated by postsynaptic connecting molecules interacting with both neuroligin-1 and N-cadherin. Postsynaptic scaffolding proteins binding to neuroligin-1 such as S-SCAM (MAGI-2) have been hypothesized to be able to link the two adhesion systems via binding to δ-catenin or β-catenin (25)(26)(27)(28)(29). To examine the potential role of S-SCAM, we expressed truncated forms of S-SCAM that were designed to inhibit protein interactions of S-SCAM in a dominant-negative manner.…”
Section: Resultsmentioning
confidence: 99%
“…The MAGI type postsynaptic scaffolding protein S-SCAM (26,29) has been described to potentially interact with catenins via binding with its PDZ5 domain to the PDZ-binding domains of β-catenin and δ-catenin (28,40). Furthermore, S-SCAM has been suggested to bind with its WW and PDZ1 domain to neuroligin-1 (27).…”
Section: Discussionmentioning
confidence: 99%
“…MAGI2 has been implicated in both glutamatergic (Deng et al, 2006) and GABAergic pathways (Sassoe-Pognetto et al, 2011). SNPs of MAGI2 have been associated with performance in the Wisconsin Sorting Card Test (WCST) in patients with SCZ (Koide et al, 2012), whereas in animal models it was shown to modulate long-term memory and associative learning (Emtage et al, 2009;Stetak et al, 2009).…”
Section: Discussionmentioning
confidence: 99%